2020
DOI: 10.1002/admt.201901037
|View full text |Cite
|
Sign up to set email alerts
|

Ion‐Selective Sensors Based on Laser‐Induced Graphene for Evaluating Human Hydration Levels Using Urine Samples

Abstract: Complex graphene electrode fabrication protocols including conventional chemical vapor deposition and graphene transfer techniques as well as more recent solution‐phase printing and postprint annealing methods have hindered the wide‐scale implementation of electrochemical devices including solid‐state ion‐selective electrodes (ISEs). Herein, a facile graphene ISE fabrication technique that utilizes laser induced graphene (LIG), formed by converting polyimide into graphene by a CO2 laser and functionalization w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
33
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 87 publications
(67 reference statements)
1
33
0
Order By: Relevance
“…Other groups have modified DLW-created carbon electrodes with copper nanoparticles alone or in combination with diamine oxidase to detect glucose or biogenic amines respectively [ 17 , 18 ]. The group of Claussen has used LIG to make ion-selective electrodes for the detection of ammonium and nitrate in soil [ 19 ] or ammonium and potassium in human urine [ 20 ]. Cardoso et al and Beduk et al reported the successful use of molecularly imprinted polymers (MIP) on LIG electrodes to detect chloramphenicol and bisphenol A, respectively [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…Other groups have modified DLW-created carbon electrodes with copper nanoparticles alone or in combination with diamine oxidase to detect glucose or biogenic amines respectively [ 17 , 18 ]. The group of Claussen has used LIG to make ion-selective electrodes for the detection of ammonium and nitrate in soil [ 19 ] or ammonium and potassium in human urine [ 20 ]. Cardoso et al and Beduk et al reported the successful use of molecularly imprinted polymers (MIP) on LIG electrodes to detect chloramphenicol and bisphenol A, respectively [ 21 , 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…[ 78–81 ] Until now, LIG has been applied in versatile flexible sensors to measure strain, [ 82,83 ] pressure, [ 84 ] humidity, [ 85 ] temperature, [ 86 ] sweat biomarkers, [ 87 ] and urine. [ 88 ] Representative research has focused on employing LIG for voice recognition, [ 89 ] human sweat analysis, [ 77,90 ] and gas sensing. [ 76,91 ] For instance, Tao et al.…”
Section: Functional Nanomaterials and Structures For Versatile Flexible Sensorsmentioning
confidence: 99%
“…[ 1–4 ] It has been developed to be the core materials of flexible electronics, such as radio frequency identification device (RFID), flexible circuit, transparent electrode, and especially wearable sensors. [ 5–8 ] The graphene‐based sensors have been researched widely in recent years, including strain sensors, [ 9–15 ] gas sensors, [ 16–18 ] chemical sensors, [ 19–21 ] and biological sensors, [ 22–24 ] etc. Wherein, graphene‐based strain sensor is the most popular with the researchers, owing to its high sensibility to tactile.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, the graphene or graphene oxide has been applied to detect dopamine, glucose, deoxyribonucleic acid, heavy metal ions, toxic chemicals, and so forth. [ 22–24 ]…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation